Thermal degradation of waste plastics under non-sweeping atmosphere: Part 2: Effect of process temperature on product characteristics and their future applications. (1st May 2020) - Singh, Rohit Kumar; Ruj, Biswajit; Sadhukhan, Anup Kumar; Gupta, Parthapratim
Abstract: The current energy demand and diminishing conventional fuels have forced researchers to find an alternative source of energy. Waste to energy is the current trend for converting waste materials (plastic waste) into valuable fuels. This article mainly discussed the detailed characterization of the pyrolytic products, their comparative analysis and the reaction mechanism at varying operating temperature. This article is a successor of part 1, which primarily focused on the characterization of different waste plastics, their TG analysis, the effect of reactor temperature on yield analysis in a batch reactor and their detailed degradation mechanism. Furthermore, the results presented in this article report the characterization of products at three processing temperatures of 450, 500 and 550 °C. The pyrolytic oils from all wastes excluding PS show a very low density ranging from 0.71 to 0.76 kg/m 3, whereas PS pyrolytic density is reported between 0.86 and 0.88 kg/m 3 . The viscosity of oils increases with an increase in the processing temperature and is similar to the conventional fuels. The FTIR analysis of the products (oil & gases) obtained from HDPE, PP and mixed plastic waste (MIX) shows a large presence of alkanes and a higher presence of aromatics. PS analysis reported a large presence of aromatics ( 75%). The GC-MS analysis of all pyrolytic oils from waste plastics, simulated wastes (virgin plastics) and distilled fraction of MIX pyrolysis oil is compared. The GC analysis of non-condensable gases at all processing temperature reports that MIX produce the maximum H2 ; HDPE, PS and MIX produces a high amounts of CH4 too. The formation of lower hydrocarbons (C5 –C12 ) in pyrolysis oil shows a trend as MIX > PP > PS > HDPE, while for the heavier hydrocarbons (>C19 ) it is HDPE > PP > PS > MIX. The potential of the utilization of these products has been discussed in different sectors for future research. Graphical abstract: Image 1 Highlights: Physical characterization of pyrolysis oils obtained at 450, 500 and 550 °C. Comparative GC-MS analysis of oils obtained from waste HDPE, PP, PS & MIX plastics. Comparative investigation of FTIR analysis of plastic waste oils. Analysis of pyrolysis gases from HDPE, PP, PS & MIX at different temperatures. Online temporal FTIR analysis of pyrolysis gases and their comparison.